Reactivation of denatured proteins by 23S ribosomal RNA: role of domain V. - Chattopadhyay, S (1996)
Escherichia coli ribosome, its 50S subunit, or simply the 23S rRNA can reactivate denatured proteins in vitro. Here we show that protein synthesis inhibitors chloramphenicol and erythromycin, which bind to domain V of 23S rRNA of E. coli, can inhibit reactivation of denatured pig muscle lactate dehydrogenase and fungal glucose-6-phosphate dehydrogenase by 23S rRNA completely. Oligodeoxynucleotides complementary to two regions within domain V (which cover sites of chloramphenicol resistant mutations and the putative A site of the incoming aminoacyl tRNA), but not to a region outside of domain V, also can inhibit the activity. Domain V of 23S rRNA, therefore, appears to play a crucial role in reactivation of denatured proteins.